Historical Perspective on the DNA Damage Response - Hanawalt, Philip C. (DNA Repair (Amst), 2015)
The DNA damage response (DDR) has been broadly defined as a complex network of cellular pathways that cooperate to sense and repair lesions in DNA. Multiple types of DNA damage, some natural DNA sequences, nucleotide pool deficiencies and collisions with transcription complexes can cause replication arrest to elicit the DDR. However, in practice, the term DDR as applied to eukaryotic/mammalian cells often refers more specifically to pathways involving the activation of the ATM (ataxia-telangiectasia mutated) and ATR (ATM-Rad3-related) kinases in response to double-strand breaks or arrested replication forks, respectively. Nevertheless, there are distinct responses to particular types of DNA damage that do not involve ATM or ATR. In addition, some of the aberrations that cause replication arrest and elicit the DDR cannot be categorized as direct DNA damage. These include nucleotide pool deficiencies, nucleotide sequences that can adopt non-canonical DNA structures, and collisions between replication forks and transcription complexes. The response to these aberrations can be called the genomic stress response (GSR), a term that is meant to encompass the sensing of all types of DNA aberrations together with the mechanisms involved in coping with them. In addition to fully functional cells, the consequences of processing genomic aberrations may include mutagenesis, genomic rearrangements and lethality.